Effectively engaging faith-based leaders on syringe services programs: U.S. pastors' knowledge, perceptions, and questions - Betsy Smither; Philip M. Reeves; Jennifer Reynolds (BMC, 2024)
Abstract Objective To identify faith-based leaders' (FBLs') knowledge, perceptions, and questions about syringe services programs (SSPs). Methods We conducted a one-time, national online survey of 461 Christian FBLs August-September 2022. Results 56% of FBLs agreed they support having SSPs in their communities; only 7% strongly disagreed. We identified 15 main questions FBLs have about SSPs. We found statistically significant differences based on FBL Protestant affiliations. Mainline FBLs are more knowledgeable about SSPs, likely to believe a larger number of SSP services would benefit their community, supportive of SSPs, interested in data related to SSPs, and likely to look to local public health officials to shape their opinions on SSPs compared with non-mainline FBLs. Conclusions SSP advocates can address questions that FBLs have about SSPs before beginning outreach. By understanding common Protestant denominational affiliations, advocates can focus initial engagement efforts on FBLs in their communities who are more likely to support SSPs. Our findings suggest that local public health officials can influence FBLs' opinions about SSPs.